Scout Extracurricular Program to Develop Student Skills and Leadership at Elementary Schools - Sabarhati, Susi (International Proceedings of Nusantara Raya, 2024)
The primary function of the after-school Scouting program in elementary schools is the targeted development of students’ leadership skills. Students are encouraged to develop skills in organizing, taking initiative, and solving problems through various activities, including discipline training, collaboration, and real-life scenario simulations. The purpose of this study was to examine the impact of the after-school Scouting program on the interpersonal, leadership, and social competencies of elementary school children. Participant surveys, in-depth interviews with scout leaders, and field observations were part of the research process. According to the study authors, scout participants tend to have higher levels of self-confidence, group leadership skills, and decision-making abilities. Furthermore, this curriculum helps shape children’s personalities to be more independent, self-controlled, and responsible, all of which are important foundations for future leadership growth. In this way, the Scouting program serves as a powerful tool for shaping young people’s character and disposition toward leadership. The results of this study indicate that the after-school Scouting program helps elementary school students develop their leadership skills and character, and also encourages them to become involved members of society.